Trends in Working Hours in OECD Countries - Evans, John M.. (OECD Labour Market and Social Policy Occasional Papers, 2001)
In recent years, the decline in average annual hours of work per person in employment, which can be traced back for over a century, has slowed. In some countries, there has even been an increase in the average annual hours per person employed. In countries where continuing falls can be observed, this can be traced to legal action (for example, France, Japan and Portugal) or to particularly vigorous negotiation between the social partners (for example, Germany and the Netherlands). The United States and Sweden both show an increase in average annual hours, in the first case due partly to an increase in overtime hours, in the second to an increase in the hours worked by part-time workers. For the European countries, the paper shows how the pattern of change in weekly working hours can be linked, inter alia, to the institutional arrangements applying in the different countries. Part-time working has both exerted downward pressure on average working hours and been an important ...